Triggering receptor expressed on myeloid cells 2 deficiency exacerbates injury-induced inflammation in a mouse model of tauopathy - Katsumoto, Atsuko; Kokiko-Cochran, Olga N.; Bemiller, Shane M.; Xu, Guixiang; Ransohoff, Richard M.; Lamb, Bruce T. (Frontiers in Immunology, 2022)
Traumatic brain injury (TBI) promotes several Alzheimer’s disease-like pathological features including accumulation of microtubule-associated protein tau (MAPT) within neurons. Especially, macrophage activation in injured hTau mouse model of tauopathy suggests that there is a correlation between MAPT pathology and alterations in macrophage activation following TBI. Triggering receptor expressed on myeloid cells 2 (TREM2) is a critical regulator of microglia and macrophage phenotype but its mechanisms on TBI remain unclear. To address the association with TREM2 in TBI and MAPT pathology, we studied TREM2 deficiency in hTau mice (hTau;Trem2-/-) 3 (acute phase) and 120 (chronic phase) days after experimental TBI. At 3 days following injury, hTau;Trem2-/- mice exhibited reduced macrophage activation both in the cortex and in the hippocampus. However, to our surprise, hTau;Trem2-/- mice exposed to TBI augments macrophage accumulation in the corpus callosum and white matter near the site of tissue damage in a chronic phase, which results in exacerbated axonal damage, tau aggregation and impaired neurogenesis. We further demonstrate that TREM2 deficiency in hTau injured mice promotes neuronal dystrophy in the white matter due to an impaired apoptotic cell clearance by phagocytosis. Remarkably, hTau;Trem2-/- exposed to TBI failed to restore blood-brain barrier integrity. These findings imply that TREM2 deficiency accelerates inflammation and neurodegeneration through attenuated phagocytosis and continuous cell infiltration, thus exacerbating tauopathy in hTau TBI mice.